Perancangan Eksperimen untuk Meningkatkan Kualitas Ketangguhan Material dengan Pendekatan Analisis General Factorial Design (Studi Kasus: Produk Solid Surface) - Salomon, Lithrone Laricha; Kosasih, Wilson; Angkasa, Sauw Oscar (Universitas Katolik Parahyangan, 2015)
PT WLS is a company that produce solid surface product. The variance of shape and design that canbe produced is very high and can be customized to the demand. The problem that occur in this company isthat sometimes the product fractured during delivery and production. To cope this problem, an experimentdesign with General Factorial Design is used to determine the best material composition that can increase thetoughness of the material. Two factors are determined to be the main factors that determine the toughnessof the materials which is the amount of hardener and the type of material used. Charpy test was used todetermine the toughness of the samples with a 55 mm x 10 mm x 10 mm dimension. Based on the analysisdone, the amount of catalyst, the type of material used, and the interaction between those two factors have asignificant effect to the materials toughness value and to get the optimal result for a 100 mm x 100 mm x 9mm sample, it was advised to use 3 ml of hardener and Al(OH)3 with HWF specifications.